Reconstruction of the Provisions on Victims and Heirs of Road Traffic Accident Victims in the Road Traffic Accident Fund Law - Bakti Prasetyo; Zaenal Mahmudi; Mustafa Lutfi (International Journal of Law, Crime and Justice, 2026)
A traffic accident is a social risk event that causes serious losses, either in the form of injury, loss of property, or death of a family member. The State provides protection through the Road Traffic Accident Fund as stipulated in Law Number 34 of 1964 and Government Regulation Number 18 of 1965. However, in practice, the regulation of the status of victims and the coverage of the heirs of the beneficiaries still raises juridical and social problems because they do not fully reflect substantive justice. This study aims to analyze the concept of victims and heirs in the applicable Road Traffic Accident Fund regulations, as well as formulate a more equitable reconstruction of the regulation. This research is normative legal research with a legislative, conceptual, and comparative approach. Analysis is carried out on positive legal norms and social realities that develop in society. The results of the study show that the definition of victim and the limitation of the coverage of heirs in the current positive law are narrow and administrative, so they are less responsive to the complexity of social relations and the economic dependence of the families of traffic accident victims. The mismatch between normative boundaries and social realities has implications for the non-achievement of the goals of social protection and substantive justice. Therefore, this study offers a reconstruction of the interpretation of the concept of victims and an expansion of the coverage of heirs that is more responsive, inclusive, and oriented towards social protection.